Quasiperiodic solutions of degenerate linear systems of second-order ordinary differential equations - Er’omenko, V. O.; Aliluiko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish sufficient conditions for the existence of quasiperiodic solutions of a system of ordinary second-order differential equations with degenerate symmetric matrix of the second derivatives for an arbitrary quasiperiodic inhomogeneity.